Locus, Sanctus, et Virtus: Monastic Surnaming in Late Medieval and Early Tudor England Reviewed - Thornton, David E. (The journal of medieval monastic studies, 2021)
This article examines the apparent practice among monks and regular canons in England before the Dissolution of dropping their family surnames on admission/profession, and adopting instead a new "monastic byname", derived from a place name (toponym) or, by the late fifteenth century onwards, from a saint's name (hagionym) or a virtue. The article begins by reviewing evidence that this onomastic practice existed and determining how widespread it was. The nature and distribution of the toponymic, hagionymic, and virtue bynames are then examined in turn. The article concludes by considering the underlying reason for the adoption of monastic bynames and argues that this practice served as a means of reflecting symbolically the new monk's or canon's separation from lay society, and from his family in particular, and his incorporation into the monastic community.